Physical Quality Characteristics of Pure and Impure Trigona Bee Honey - N. Nuraini; H. Hastuti; H. Husnaeni (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2021)
This study aims to determine the physical quality characteristics of pure and impure honey bee Trigona. The material used in this research is pure honey and impure honey. This study consisted of 2 treatments with five replications where X1 (pure honey) and X2 (unpure honey). Parameters observed included soluble test, heating test, hexagon test, and ant test. Data analysis using t-test. Based on the results of the analysis of variance, it shows that each soluble test is X1 = 1.6 and X2 = 3.8, the heating test is X1 = 4.6 and X2 = 2.4, the hexagon test is X1 = 2 and X2 = 1, 8, the ant test is X1 = 3.2 and X2 = 4.2. The study results can be concluded that the effectiveness of the honey purity test using several simple methods that most meet the requirements are the soluble test method, the heating test method, and the ant test. In contrast, the hexagon test does not give a response at all.